Disaster Relief as Indonesia Soft Power Diplomacy Case of Cyclone Pam in Vanuatu - Vrameswari Omega Wati; Deffi Ayu Puspito Sari; Sobar Sutisna (International Journal of Multi Discipline Science, 2018)
Natural disasters are part of non-traditional threats that must be faced by the countries in the world. To handle this issue, the international community should improve their relations through cooperation. On March 14, 2015, Vanuatu, suffered Cyclone Pam which resulted in casualties and damage in the region. On behalf of humanity, Indonesia, as a country with great attention to disaster and who has the same of Melanesia brotherhood provide disaster relief to Vanuatu. The method used is qualitative. This paper attempts to answer how the process of providing disaster relief by Indonesia to Vanuatu and how disaster relief can be seen as a form of Indonesia’s soft power diplomacy to Vanuatu. Data was obtained through in-depth interviews and literature study. The results showed the process of disaster relief is carried out in accordance with the three stages in the Emergency Decision Making Process which are assessing the situation and needs; determining goal and assistance; and implementing of response plans. Disaster relief is also a kind of Indonesia soft power diplomacy to Vanuatu to show a sense of humanity, to enhance friendship, and to maintain the integrity of the Republic of Indonesia sovereignty. After the disaster relief given by Indonesia government, relations between Indonesia and Vanuatu are starting to show shades of improvement. Cyclone Pam that happened in Vanuatu can be seen as a catalyst to improve the chances of good relations between Indonesia and Vanuatu and building cooperation in disaster management.